Menstrual cup webinar series: A developing model of modified pre- and post-tests in the online teaching-learning of primary health care workers - Arti Gupta; Rajeev Aravindakshan; Vijayan Sharmila; B Venkatashiva Reddy; Yamini Marimuthu; Navya Krishna Naidu (Wolters Kluwer Medknow Publications, 2023)
Menstrual hygiene management, especially in resource-limited settings, is challenging. The acceptability of the menstrual cup is increasing recently in western countries whereas, in developing countries like India, the awareness, acceptability, and use of menstrual cups are very limited. We assessed the effectiveness of modified pre-post-test teaching-learning methodology in an online webinar series on menstrual cups using Moore's outcome assessment. An online webinar series on menstrual hygiene and the menstrual cup was conducted to raise awareness about the usage of menstrual cups among the health care workers like Auxiliary Nurse Midwife (ANMs), Accredited Social Health Activist (ASHAs), and Anganwadi Workers (AWWs) of the Guntur district, Andhra Pradesh, India. The questions of modified pre- and post-test were displayed. The questions were displayed to participants using the polling option in zoom. A total of 1597 health care workers participated in the menstrual cup webinar series. Of the total, 72.7% of participants responded to the job title question of which ASHA, ANMs, and AWWs were 16.8%, 34.2%, and 41.9%, respectively. The baseline knowledge of menstrual cups among primary health care workers for "heard of the menstrual cup" and "ever used/know anyone using menstrual cup" was 36.89% and 11.67%, respectively. After the webinar among the primary health care workers, the maximum gain in knowledge was seen for "menstrual cup can be cleaned in the home," 94.53%, and the minimum gain in knowledge was on "unmarried girls can use menstrual cups," 50.42%. The modified pre- and post-test model predicted an overall 50 percent rise in the knowledge of primary health care workers by the webinar series about a different aspect of the menstrual cup.As online webinar providers aim to provide more performance-based learning activities, current approaches to continuing medical education may become obsolete. The single most essential shift in online webinar planners can make is to incorporate modified pre-and post-test to allow for interactive and formative assessment during webinar activities.